Gene Expression Profiling Reveals Clear Differences Between EBV‐Positive and EBV‐Negative Posttransplant Lymphoproliferative Disorders. Issue 5 (14th March 2013) - Morscio, J.; Dierickx, D.; Ferreiro, J. F.; Herreman, A.; Van Loo, P.; Bittoun, E.; Verhoef, G.; Matthys, P.; Cools, J.; Wlodarska, I.; De Wolf‐Peeters, C.; Sagaert, X.; et al.
Abstract : Posttransplant patients are at risk of developing a potentially life‐threatening posttransplantation lymphoproliferative disorder (PTLD), most often of diffuse large B cell lymphoma (DLBCL) morphology and associated with Epstein–Barr Virus (EBV) infection. The aim of this study was to characterize the clinicopathological and molecular‐genetic characteristics of posttransplant DLBCL and to elucidate whether EBV(+) and EBV(−) posttransplant DLBCL are biologically different. We performed gene expression profiling studies on 48 DLBCL of which 33 arose posttransplantation (PT‐DLBCL; 72% EBV+) and 15 in immunocompetent hosts (IC‐DLBCL; none EBV+). Unsupervised hierarchical analysis showed clustering of samples related to EBV‐status rather than immune status. Except for decreased T cell signaling these cases were inseparable from EBV(−) IC‐DLBCL. In contrast, a viral response signature clearly segregated EBV(+) PT‐DLBCL from EBV(−) PT‐DLBCL and IC‐DLBCL cases that were intermixed. The broad EBV latency profile (LMP1+/EBNA2+) was expressed in 59% of EBV(+) PT‐DLBCL and associated with a more elaborate inflammatory response compared to intermediate latency (LMP1+/EBNA2−). Inference analysis revealed a role for innate and tolerogenic immune responses (including VSIG4 and IDO1) in EBV(+) PT‐DLBCL. In conclusion we can state that the EBV signature is the most determining factor in the pathogenesis of EBV(+) PT‐DLBCL. Abstract : Gene expression profiling reveals clear differences between EBV‐positive and EBV‐negative posttransplant lymphoproliferative disorders.